Identification of genetic alterations in couples and their products of conceptions from recurrent pregnancy loss in North Indian population - Srivastava, Priyanka; Bamba, Chitra; Chopra, Seema; Rohilla, Minakshi; Chaudhry, Chakshu; Kaur, Anupriya; Panigrahi, Inusha; Mandal, Kausik (Frontiers in Genetics, 2023)
Recurrent Pregnancy Loss (RPL) is one of the most common pregnancy-related complications, which can be stressful and emotionally draining for a couple. Genetic alterations which are responsible for RPL, can be present in either of the 3 genomes: mother, father and their fetuses. In addition, environmental factors interacting with these three genomes can affect germline cells. Next Generation Sequencing (NGS; couple exome and TRIO exomes) in combination with cytogenetic tests (Karyotyping and chromosomal microarray (CMA)) might aid in understanding the underlying etiology of RPL. With this aim, in present study, we recruited 61 couples with RPL and 31 products of conceptions (POCs). In 6 individuals out of 61 couples (5%), abnormality in karyotype was detected. Among 116 normal karyotypes, there were 11heteromorphisms (9.5%), for which the couples had to be counselled and reassured. Out of 31 POCs, 10 were excluded because of maternal cell contamination (MCC) (around 30%) and one had major aneuploidy. CMA in POCs identified pathogenic copy number variations (CNVs) in 25% of cases (5/20), variant of unknown significance (VUS) in 20% of cases (4/20). Autosomal trisomy was the most frequent chromosomal abnormality diagnosed. NGS was done to establish single-gene causes of RPL. Couple exome sequencing was done in 20 couples, 14 were found to be carriers for autosomal recessive conditions. Total 50 potential disease-causing variants in 40 genes were identified in 33 out of 40individuals (82.5%). Putative causative variants were identified in 37.5% of the TRIO cases (3/8). Mutations in few important genes (SRP54, ERBB4, NEB, ALMS, ALAD, MTHFR, F5, APOE) which are involved in vital pathways, early embryonic development and fetal demise were identified in the POCs. It enhances our understanding of prenatal phenotypes of many Mendelian disorders. These mutated genes may play an auxiliary role in the development of treatment strategies for RPL. There was no correlation of number of abortions with etiological yield of any technique to detect the cause of RPL. This study shows the utilization of combination of techniques in improving our understanding of the cause of early embryonic lethality in humans.